Let and denote the sides of a triangle opposite to the angles and respectively.
Compute the value of the summation above, where and .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let S= ∑ r = 0 4 ( 4 C r ) b 4 − r c r cos ( r B − ( 4 − r ) C )
and T= ∑ r = 0 4 ( 4 C r ) b 4 − r c r sin ( r B − ( 4 − r ) C )
then S + iT= ∑ r = 0 4 ( 4 C r ) b 4 − r c r e i ( r B − ( 4 − r ) C )
=> S+iT= ( c e i B + b e − i C ) 4
=> S+iT= ( ( c cos B + b cos C ) + i ( c sin B − b sin C ) ) 4
since according to sine rule sin C c = sin B b => ( c sin B − b sin C ) =0
=> T=0 whereas S= a 4 [ using Projection formula]
=> S= 5 4 = 625